Rapid Fractionation of Wheat Leaf Protoplasts Using Membrane Filtration : The Determination of Metabolite Levels in the Chloroplasts, Cytosol, and Mitochondria - Lilley, Ross McC. (1982)
A technique is presented for measuring the in vivo metabolite levels in the chloroplast stroma, the cytosol, and the mitochondrial matrix of wheat (Triticum aestivum, var `Timmo') leaf protoplasts, in which membrane filtration is used to prepare fractions enriched in the different subcellular fractions within 0.1 seconds after disruption of the protoplasts. By closing a syringe, protoplasts are forced through a net and disrupted, diluting the cytosol into the medium and also releasing intact chloroplasts and mitochondria which can then be immediately removed on membrane filters placed behind the nylon net. By varying the membrane filters, different filtrates are obtained corresponding to (a) mainly cytosol, or (b) cytosol and mitochondria with only low levels of chloroplasts; alternatively, (c) the entire protoplast contents are obtained by omitting the filters. The filtrates are immediately split, half flowing into HClO(4) where they are immediately quenched for subsequent metabolite analyses; the other half flows into detergent and is used to monitor the exact distribution of marker enzymes in each individual fractionation. Using the measured distributions of metabolite and of marker enzymes in the three filtrates, the subcellular distribution of the metabolite can be algebraically calculated. The method is presented using ATP as an example. The quench time (0.1 second) made possible by membrane filtration is considerably faster than has been possible in the previously developed techniques using silicone oil centrifugation for chloroplasts (1 second) or mitochondria (1 minute). This rapid quench makes it possible to investigate subcellular pools which have a rapid turnover, like the adenine nucleotides.